Proses Perancangan Konten Motion Graphic Untuk ERP DI Instagram - Erlangga Satrio Yudha; Restu Ismoyo Aji (Journal of Creative Student Research, 2023)
Motion graphics are an important component in a company called ERP Indonesia, because it has a company marketing strategy in the modern digital era, ERP is a company that operates in the field of consulting services regarding Branding (Brand Consultant) (Eka Reka Palakerti) is already engaged in the field of Brand Consultancy since November 30 2019 in Semarang and Tangerang, has an Instagram account which is used as a medium for promoting its services, and in this content uses animated videos based on motion graphics. ERP has increased visual appeal in marketing, increased consumer engagement, and optimized the efficiency of message communication via social media.